The The Role of Entrepreneurial Orientation and Competence in Business Performance Through HR Readiness as A Mediator in SMEs - Murniningsih, Rochiyati; Dzulfikar, Yusuf Rifqi (Innovation, Technology, and Entrepreneurship Journal, 2026)
This study aims to analyze the effect of entrepreneurial orientation and entrepreneurial competence on business performance through human resource readiness as a mediator among SMEs actors. The research method used is quantitative. Data analysis of 170 respondents was conducted using the Structural Equation Modeling (SEM) approach using the AMOS program. The results of this study indicate that entrepreneurial orientation and entrepreneurial competence have a positive and significant effect on human resource readiness. Furthermore, human resource readiness has a positive and significant effect on business performance. The HR readiness variable mediates the effect of on Business Performance and the effect of Entrepreneurial Competence on Business Performance